Copper-Lithium-Doped Nanohydroxyapatite Modulates Mesenchymal Stem Cells Homing to Treat Glucocorticoids-Related Osteonecrosis of the Femoral Head - Li, Qianhao; Yang, Zhouyuan; Wei, Zhun; Li, Donghai; Luo, Yue; Kang, Pengde (Frontiers in Bioengineering and Biotechnology, 2022)
In situ tissue regeneration has been demonstrated to promote bone repair. To identify a better approach for treating osteonecrosis of the femoral head (ONFH), we prepared scaffolds using copper-lithium-doped nanohydroxyapatite (Cu-Li-nHA), which has the potential to modulate mesenchymal stem cells (MSCs) homing. The scaffold was fabricated using the gas foaming method and the migration, angiogenesis, and osteogenesis activities of MSCs were detected using Transwell assays, tube formation assays, alkaline phosphatase and alizarin red S staining, respectively. We then implanted the Cu-Li-nHA scaffold into the femoral heads of ONFH rabbits, and CFSE labeled exogenous MSCs were injected intravenously to verify cell homing. The repair effect was subsequently examined using micro-CT and histological analysis in vivo. The results showed that Cu-Li-nHA significantly promoted MSCs migration and homing by upregulating the HIF-1α/SDF-1 pathway. The Cu-Li-nHA group showed optimal osteogenesis and angiogenesis and greater improvements in new bone formation in ONFH rabbits. To summarize, Cu-Li-nHA promoted homing and induced the osteogenic differentiation of MSCs, thereby enhancing bone regeneration during ONFH repair. Thus, Cu-Li-nHA implantation may serve as a potential therapeutic strategy for ONFH in the future.